Multidisciplinary diagnosis and treatment of oral squamous cell carcinoma after oro-antral communication: 2 years of follow-up - Riegel, Carolina; Grando, Camila; Brum, Renata Scheeren; Brucker, Márcia Rejane; Maito, Fabio Luiz (Journal of Oral Diagnosis, 2020)
Introduction: Oral squamous cell carcinoma (OSCC) is the most common malignant oral neoplasm and its early diagnosis is preferred, since late diagnosis requires a much more complex treatment. The multilations caused by OSCC and its treatment can strongly affect patients quality of life, which demands reconstructive oncology plastic surgery and prosthetic rehabilitation. Objective: the aim of the present case report is to present the results of a late diagnosis of OSCC, its treatment and oral rehabilitation. Case report: 70-year old male smoker and alcoholic patient attended Department of Oral Surgery with main complain of odynophagia and dysphagia. Patient reported that has noticed an intra-oral lesion approximately one year before. Extra-oral examination revealed infarcted lypmph nodes, intra-oral examination showed a lesion with irregular and hardened edges of rose coloration with ulceration on the surface measuring 4 cm x 3 cm in palate. An incisional biopsy was performed and additional histophatological exam was realized. Therefore, the diagnosis of OSCC was settled. Patient was submitted to partial maxillectomy and neck lymphnodes deflation on the right side, combined with radiotherapy and chemotherapy. As a treatment sequel, an oro-antral communication was developed. A palatal obturator prosthesis was manufactured. Instructions of oral hygiene included chlorhexidine gluconate 0,12% for mouth rinsing. Followup appointments were realized regularly during 19 months. Results: Surgery accompanied by radiotherapy and chemotherapy were efficient in treating OSCC. The palatal obturator prosthesis provided adequate esthetic and functional results, improving patients quality of life. After 19-months follow-up treatment, no recurrent lesions were developed and the obturator was adequately adapted. Conclusions: As early diagnosis was not possible, OSCC was properly treated by surgical enucleation accompanied by radiotherapy and chemotherapy. Its sequels were adequately rehabilitated through palatal obturator prosthesis.